Characterization and investigation of the mesogenic, thermo-morphologic and thermotropic properties of new chiral (S)-5-octyloxy-2-[{4-(2-methylbuthoxy)-phenylimino(methyl]phenol liquid crystalline compound - Eran, Belkiz Bilgin; Nesrullajev, Arif; Canli, Nimet Yilmaz (ELSEVIER SCIENCE SA, 2008)
Synthesis, characterization and investigation of the mesogenic, thermo-morphologic and thermotropic properties of a new chiral liquid crystalline compound are presented in this work. This new compound has prolate molecules and exhibits the chiral smectic C* mesophase in a sufficiently large temperature interval. Two types of solid crystalline phases have been found in this compound. Typical textures and temperatures of the direct and reverse phase transitions, taking place in the compound, are given. Typical peculiarities for the first-order transition between the smectic C* mesophase and isotropic liquid have been observed. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: optical materials; organic compounds; optical properties; phase equilibria; NEMATIC-ISOTROPIC LIQUID; PHASE-TRANSITIONS; COPPER(II) COMPLEXES; PECULIARITIES; DERIVATIVES; DSC; Materials Science